1999
DOI: 10.1038/sj.cdd.4400582
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO): an effector of apoptosis

Abstract: It is appreciated that the production of nitric oxide (NO) from Larginine metabolism is an essential determinate of the innate immune system, important for nonspecific host defense, as well as tumor and pathogen killing. Cytotoxicity as a result of a substantial NO-formation is established to initiate apoptosis, characterized by upregulation of the tumor suppressor p53, changes in the expression of pro-and anti-apoptotic Bcl-2 family members, cytochrome c relocation, activation of caspases, chromatin condensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
189
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(206 citation statements)
references
References 54 publications
(69 reference statements)
7
189
0
3
Order By: Relevance
“…67,68 Depending on cell type and intracellular redox status, NO can induce apoptosis or necrosis, acting as a molecular switch between the 2 processes. 61 RES increased NO production by MCF-7 cells, in particular at concentrations that also altered DC(m) and ROS generation and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Depending on cell type and intracellular redox status, NO can induce apoptosis or necrosis, acting as a molecular switch between the 2 processes. 61 RES increased NO production by MCF-7 cells, in particular at concentrations that also altered DC(m) and ROS generation and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a pathophysiological molecular effector, the chemical biology of NO can be divided into direct and indirect pathways. NO is a high energy radical and has the ability to cause DNA fragmentation by direct attack or indirect activation of serious signal transduction [3,37]. Previous studies have reported that NO induced by proinflammatory cytokines, tumor necrosis factor-ell, interleukin-1p and interferon-y, or an NO donor, Snitroso-N-acetyl-D,L-penicillamine would lead to DNA fragmentation and cell death of a mouse clonal osteogenic cell line, MC3T3-El cell [11,27].…”
Section: Controlmentioning
confidence: 99%
“…[8,9] It should be also noted that NO, which is produced by a number of nitric oxide synthase (NOS) enzymes from larginine in the body, [10] plays a major role as a signaling molecule in biological signal transducing systems, for example, in blood pressure regulation, [11,12] neurotransmission, [13,14] inflammatory response, [15,16] as well as necrosis [17] and apoptosis. [18,19] Nitric oxide is therefore essential in biological systems, but both its excess as well as deficiency leads to pathologies.…”
Section: Introductionmentioning
confidence: 99%